Class, Popular Culture, and the Academy: Critical Comments of Scholars from the Working-Class - Robin Redmon Wright (Adult Education Research Conference, 2010)
Twenty-five self-identified working-class scholars were interviewed about their life histories in an effort to understand their career choice. Participants credited the incidental and informal learning they received from consuming film, television shows, popular music, comic books and novels as expanding their world view and instilling a desire to succeed academically.